Evaluation of a head-to-head study of lisdexamfetamine dimesylate and atomoxetine. (September 2014) - Banaschewski, Tobias; Rothermel, Boris; Poustka, Luise
<x xml:space="preserve">Abstract</x> Here, we evaluate a report of a head-to-head study of the prodrug stimulant lisdexamfetamine dimesylate (LDX) and the non-stimulant atomoxetine hydrochloride (ATX) in children and adolescents with attention-deficit/hyperactivity disorder (ADHD). An inadequate response to previous methylphenidate (MPH) treatment was a notable inclusion criterion. The primary efficacy outcome of a more rapid clinical response to LDX than to ATX was predictable from the known properties of the two drugs. However, secondary efficacy outcomes indicated that LDX was significantly more effective than ATX in relieving investigator-rated symptoms of ADHD, with an effect size of 0.56. Safety and tolerability profiles were consistent with the known properties of LDX and ATX. Despite some issues with the study design, the conclusion that LDX is more effective than ATX over the short term appears robust. In addition, the magnitude of improvement with both treatments indicated that previous MPH treatment is not a factor affecting the potential for patients to benefit from LDX or ATX. The results may help to inform clinical practice in Europe, where LDX is approved for treating children and adolescents with ADHD and a previous inadequate response to MPH, and in other regions where generic MPH formulations are typically the first-line therapeutic option.